Does Hashimoto's Thyroiditis Increase the Risk of Cardiovascular Disease in Young Type 1 Diabetic Patients? - Głowinska-Olszewska, Barbara; Borysewicz-Sańczyk, Hanna; Sawicka, Beata; Klonowska, Bożenna; Charemska, Dorota; Żelazowska-Rutkowska, Beata; Bossowski, Artur (Frontiers in Endocrinology, 2020)
Background: Immunological and hormonal disorders undoubtedly influence to development of atherosclerotic process. Autoimmune diseases accompanying type 1 diabetes (T1D) may accelerate atherosclerosis progression and increase the risk of cardiovascular events in future. The influence of subclinical hypothyroidism on the cardiovascular system in particular has aroused great interest. The aim of the study was to evaluate cIMT (carotid intima media thickness) of common carotid arteries and the occurrence of classical risk factors and new biomarkers of atherosclerosis in young patients with type 1 diabetes mellitus with concomitant Hashimoto disease (HD). Patients and methods: The study was performed in 50 adolescents and young adults with T1DM, mean age 17.1±3 years, with mean diabetes duration 10.5±3.3 years, including 20 patients with diagnosed Hashimoto disease HD(+) and 30 patients with no additional diseases HD(-). The control group (C) consisted of 22 healthy, age-matched volunteers. Statistical analyses included: mean HbA1c value from all years of disease, BMI, arterial pressure, lipid values, new biomarkers of atherosclerosis (hsCRP, adiponectin, myeloperoxidase, NT-pro-BNP peptide, vitamin D), and cIMT. Results: In the group of patients with T1D and HD(+) significantly higher BMI was found: 23.3±4.4 vs 21.28±2.9 in group D and 19.65±2.4 kg/m2 in group C (p=0.003) and higher waist circumference: 79±10.9 vs 75.10±7.6 in group D vs 69.0±7.4 cm in group C (p<0.001). The mean value of HbA1c was higher in group HD: 8.8% than in group T1D: 8.1% (p=0.04). Significantly higher concentration of hsCRP and lower vitamin D was observed in T1D and HD(+) in comparison to T1D and HD(-) and control group. IMT index in HD(+) group was 0.46±0.05 mm and was comparable to HD(-) group, but significantly higher than in control group: 0.41±0.03 mm (P<0.05). Conclusions: Young patients with type 1 diabetes mellitus coexisting with Hashimoto disease have higher BMI, higher waist circumference and higher HbA1c value, which all together may cause faster development of macroangiopathy in the future. Additional risk for cardiovascular disease may result from low vitamin D and increased hsCRP concentration in these group of patient. Coexistence of Hashimoto disease did not significantly affected the cIMT value in the studied population.